Дослідження характеристик чотирибойкового кувального пристрою - Коломієць, С. М. (My University, 2015)
En: The article presents the analysis of the status and results of research of characteristics of sotiropoulou forging device.
Keywords: radial forging; cotribuicao device; the center of gravity; moment of inertia; чотирибойковий кувальний пристрій; вага кувального пристрою